A comprehensive review of lysine-specific demethylase 1 and its roles in cancer. (August 2017) - Hosseini, Amir; Minucci, Saverio
Histone methylation plays a key role in the regulation of chromatin structure, and its dynamics regulates important cellular processes. The investigation of the role of alterations in histone methylation in cancer has led to the identification of histone methyltransferases and demethylases as promising novel targets for therapy. Lysine-specific demethylase 1(LSD1, also known as KDM1A) is the first discovered histone lysine demethylase, with the ability to demethylase H3K4me1/2 and H3K9me1/2 at target loci in a context-dependent manner. LSD1 regulates the balance between self-renewal and differentiation of stem cells, and is highly expressed in various cancers, playing an important role in differentiation and self-renewal of tumor cells. In this review, we summarize recent studies about the LSD1, its role in normal and tumor cells, and the potential use of small molecule LSD1 inhibitors in therapy.